Front‐ and rear‐side photoluminescence: recombination, depth profiles of excess carriers and optical band gap of Cu(In, Ga)Se2 in a three‐layer system. Issue 5 (31st January 2014) - Neumann, O.; Brüggemann, R.; Könne, N.; Bauer, G. H.
<x xml:space="preserve">Abstract</x> Spectral photoluminescence emitted from the front compared to the rear side of a semiconductor layer like a photovoltaic absorber is shown to exhibit significant differences in the high‐energy regime. This arises from the excess‐carrier depth profile and the absorption of photoluminescence photons during their way through the semiconductor layer depending on photon energy, distance to the absorber exit, and absorption coefficient.We get access to surface‐recombination velocities, the minority‐carrier diffusion length, the excess‐carrier depth profile and the optical band gap by fitting photoluminescence spectra via numerical modeling. The numerical modeling is based on an one‐dimensional three‐layer system that includes multiple reflection. This procedure is exemplarily demonstrated for a thin‐film system based on Cu(In, Ga)Se2.